Hubungan Beban Kerja Dengan Kinerja Perawat - Erwanto; Bernadeta Leviana; Nadhifah Rahmawati; Putu Sintya Arlinda Arsa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Nurses face many problems because they have many roles and responsibilities in providing services in hospitals. One of them is the excessive workload. Workload can cause stress, which leads to fatigue at work and physical or mental exhaustion, which can affect nurses' performance when providing services. The purpose of this study is to determine whether there is a relationship between the performance of nurses at